PERAN BUDAYA SEKOLAH MEMODERASI KOMPETENSI GURU DAN DISIPLIN KERJA TERHADAP KINERJA GURU ( Studi pada Guru SMP Negeri di Sub Rayon 01 Kabupaten Jepara ) (Students' Journal of Economic and Management, 2013)
This study examines the question of how the influence of teacher competence and discipline of work on teacher performance is moderated by the school culture in the teachers in SMP Negeri Sub Rayon 01 Kabupaten Jepara. The purpose of this study is to examine and analyze a). influence on the performance of teacher competence, b). disciplinary effect on kinerjaguru, c). the influence of school culture on teacher performance, d). moderating role of school culture on teacher performance competencies, and e). moderating role of school culture on teacher performance discipline. The population in this study were all teacher's status as a civil servant (PNS) who works at SMP Negeri Sub Rayon 01 Kabupaten Jepara totaled 239 teachers, using stratifiet proportional random sampling technique. Number of respondents surveyed was 149 teachers. Method of data collection using a questionnaire given to the respondents with a Likert scale in the range 1-5. Tests on instrument validity study conducted with factor analysis, Cronbach alpha reliability test, test for normality with the Kolmogorov-Smirnov method, test and test Multicollinearity Heteroskidastity are statistical tool used is multiple regression analysis, simultaneous significance test (test statistic F) and t statistical test to prove the hypothesis of the proposed research. Results of data analysis showed that the positive and significant effect of competence on teacher performance, school culture positive and significant effect on the performance of teachers, work discipline does not affect the performance of teachers and school culture on teacher performance competency moderate but not moderate disciplined school culture of work on teacher performance. Keywords: School Culture, Teacher Competence, Work Discipline and Performance Guru.